2018
DOI: 10.1186/s12917-018-1407-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic potential of Shiga toxin-producing Escherichia coli strains of caprine origin: virulence genes, Shiga toxin subtypes, phylogenetic background and clonal relatedness

Abstract: BackgroundAll over the world, Shiga toxin-producing Escherichia coli (STEC) are considered as important zoonotic pathogens. Eight serogroups have the greatest role in the outbreaks and diseases caused by STEC which include O26, O45, O103, O111, O113, O121, O145 and O157. Ruminants, especially cattle are the main reservoirs but the role of small ruminants in the epidemiology of human infections has not been thoroughly assessed in many countries. The objective of this research was to investigate the pathogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
3
12
2
Order By: Relevance
“…Goats six months and older were predominantly hosts to group B1. Our study findings are similar to [26,34,60] who found a high prevalence of the B1 group in adult goats and a few isolates of A phylogenetic group. Although the prevalence in individual species was not mentioned, Derakhshandeh et al [64] also found a predominance of group D E.coli in ruminants that included goats.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Goats six months and older were predominantly hosts to group B1. Our study findings are similar to [26,34,60] who found a high prevalence of the B1 group in adult goats and a few isolates of A phylogenetic group. Although the prevalence in individual species was not mentioned, Derakhshandeh et al [64] also found a predominance of group D E.coli in ruminants that included goats.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also detected group B2 E. coli isolates mostly in kids less than six months with the highest number of isolates being detected around the weaning period. In the previous studies evaluating E.coli isolates from goats [26,34,60,61] only one reported a few isolates belonging to phylogenetic B2 [61]. E. coli isolates belonging to group A were very few in all age groups in this study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Diversity in STEC phylogroups has been observed previously. A study of caprine-associated STEC predominantly observed phylogroup B1 isolates, with strains of phylogroup A also isolated (Jajarmi, Askari Badouei, Imani Fooladi, Ghanbarpour, & Ahmadi, 2018). A study of STEC in water used for shellfish production was identified as predominantly being of phylogoups A, B1 and D (Baliere et al, 2015), while a study of STEC in wildlife identified strains of phylogroups A, B1, B2 and D (Mora et al, 2012).…”
Section: Discussionmentioning
confidence: 99%